THE CORPORATE SOCIAL RESPONSIBILITY (CSR) MODEL OF PT INDANA IN JODIPAN TOURISM VILLAGE ‘’KAMPUNG WARNA WARNI’’ - Tiara Estu Amanda; Tomi Agfianto (Jurnal Pengembangan Kota, 2021)
The implementation of Corporate Social Responsibility (CSR) in Indonesia has not been fully implemented properly. It can see from the company's concern for the community and the environment affected by their business activities which are still considered exceptionally low. Meanwhile, the activities carried out are still philanthropic activities and do not pay attention to and fulfill the existing sustainability values. Therefore, it is essential to discuss the need for successful implementation models (best practices) in a company. One company that has succeeded in implementing CSR is PT INDANA in Kampung Warna-Warni (KWW) Jodipan Malang. GuysPro assisted this company in carrying out CSR in painting in a slum village, namely Jodipan. The impact of CSR implementation makes the village become a tourist attraction that tourist most visited when going to Malang City. This study discusses the CSR implementation model carried out by PT Indana and GuysPro in implementing this activity in Kampung Warna Warni (KWW) Jodipan, Malang. A descriptive-qualitative analysis is applied in interpreting the existing data. Meanwhile, data were obtained from field observations, in-depth interviews, and literature studies to support the research. The results obtained show that there are four stages in CSR activities carried out by PT INDANA. The four stages include the planning and implementation stages, the evaluation stage, and the reporting stage. The impact felt by the community from the CSR activities carried out is the emergence of the development of tourist attractions as a form of unexpected consequences, and the positive influence of the stakeholders involved can be felt. These stakeholders include PT INDANA, the GuysPro Group, the community, and the government as the regulator.